PENGARUH MANAJEMEN SUMBER DAYA MANUSIA TERHADAP PENINGKATAN MUTU PENDIDIKAN DI LEMBAGA PENDIDIKAN ANAK USIA DINI AL-QUR’AN (PAUD-Q) KARANGPLOSO MALANG - Lutfi Sambudi (Program Studi Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2022)
The Human resource management has an effect in the effort to improve the school quality. This is because the human resource management is all activities related to the importance of educators and school education personnel as vital resources. When the management human resource management in a school have a good quality so will be affect for the education quality. The purpose this research to know: (1) The effect human resources management on the improving school quality at the institution early childhood education Al-Qur’an Karangploso Malang (2) How is the education quality at the institution early childhood education Al-Qur’an Karangploso Malang (3) Is an effect human resources management on the improving education quality at the institution early childhood education Al-Qur’an Karangploso Malang? This research used method quantitative approach with the type ex post facto. Data collection techniques used questionnaires and documentation, with a sample on 20 samples. The data got then analyzed with the coefficient determination and simple linear regression test, using the application SPSS 26.0 for windows. The results this research show on (1) Human resource management at the institution early childhood education Al-Qur’an Karangploso is high category (2) Education quality at the the institution early childhood education Al-Qur’an Karangploso is high category (3) Human resource management has an effect 8,1% on the school quality at the institution early childhood education Al-Qur’an Karangploso. In accordance with the results of hypothesis testing that Ho is accepted and Ha is rejected. In other words, there is no significant effect between the human resource management variable (X) on the education quality variable (Y).